Єпископ Григорій Хомишин мовою матеріалів слідства (за документами Галузевого Державного архіву СБ України) - Сердюк, Н. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The selection of 9 authentic documents, which were kept in the Hryhoryi Khomyshyn’s (1867–1945) archival criminal file in Branch state archive of Security service of Ukraine, is the vivid illustration of the last years of one of the leading hierarch of Ukrainian greco-catholic (Uniat) church. It also shows us the course of Stalin’s repression against the Uniat church during the second half of 1940th.